REVEALING THE LEVELS OF REFLECTION OF PRE-SERVICE ENGLISH TEACHERS IN TEACHING PRACTICE: A CASE STUDY - Nuraeni; Mahabbah, Nurul (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2025)
This study focuses on revealing the levels of pre-service English teachers' reflection during teaching practice program. The research design used in this study was a qualitative case study using reflective teaching journals and questionnaires as data collection instruments. The participants in this study were three English language education students of the 6th semester who were conducting teaching practice. This study revealed that pre-service teachers' reflection levels were at the descriptive reflection and dialogic reflection levels. The pedagogical implication was that the reflection can help pre-service teachers develop their reflection skills by familiarizing themselves with reflection practices, making reflection as an important part of professional development, and seeking guidance from experienced teachers or mentors.